Factors Affecting Stock Prices: An Extensive Analysis of Companies Appraisal Approaches (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Examining how tax avoidance, company size, and financial performance affect stock values is the aim of this study. A thorough analysis of the 2021-2023 financial statements of infrastructure companies listed on Indonesia Stock Exchange (IDX) was conducted in order to support this study. Employing a purposive sampling methodology, the sample for this research comprised 22 infrastructure firms.Every selected entity that serves as a research sample provides the secondary data used in this study through its financial statement. To elucidate financial performance, this research utilized the following variables: Current Ratio (X1a), Debt-to-equity Ratio (X1b), Total Asset Turnover (X1c), Return on Equity (X1d), Price-earnings Ratio (X1e), and Company Size (X2) as the second independent variable, alongside Tax Avoidance (X3) as the third independent variable. The research methodology employed in this study was the panel data regression approach, utilizing the E-views 12 software to facilitate the analysis of the research outcomes. The result of the research suggest that the Random Effect Model (REM) constitutes the most efficacious analytical framework. Furthermore, the findings of the study reveal that, while the other variables did not exert an influence on stock price, both the Return-on-equity Ratio (X1d) and Company Size (X2) significantly impacted stock price.